Interleukin 3 binds to a 140-kDa phosphotyrosine-containing cell surface protein. - Isfort, R J (1988)
Interleukin 3 (IL-3) is a hematopoietic growth factor that supports the proliferation and differentiation of early hematopoietic-lineage progenitors. By using growth factor-dependent cell lines, IL-3 has been shown to induce the appearance of several phosphotyrosine-containing proteins, including a 140-kDa cell surface phosphoprotein. Here we demonstrate that the 140-kDa phosphoprotein binds IL-3 and forms a stable complex with an apparent molecular mass of 170 kDa. The possible relationship of the 140-kDa phosphoprotein to the previously described 65-kDa IL-3-binding protein is discussed.